A 0.8mm thick strip steel and its production process
Through the production process of 0.8mm thickness strip steel, combined with Fe@graphene@Zn nanosheet plating agent, the problem of insufficient hardness, strength and surface quality in the existing strip steel production process is solved, and higher mechanical properties and better surface quality are achieved to meet customers' needs for thinner and more accurate sizes.
Patent Information
- Application Number
- CN202410859118.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-28
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-06-28
AI Technical Summary
In the existing strip steel production process, the hardness and strength of hot-rolled steel plates are low, the surface quality is poor, and cannot meet customers' requirements for thinner and more accurate dimensionality.
The production process of 0.8mm thickness strip steel is adopted, including raw material treatment, hot rolling, intermediate annealing, cold rolling, hot-dip galvanizing and finished product annealing, and the bonding strength and surface quality of the galvanized layer are improved by using Fe@graphene@Zn nanosheets as plating agents.
The prepared 0.8mm thickness strip steel has good mechanical properties, high hardness, stability, oxidation resistance and processability, which can meet customers' requirements for thinner and more accurate dimensions and has broad application prospects.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of strip steel, and in particular to a strip steel with a thickness of 0.8 mm and a production process thereof. Background Art
[0002] Strip steel is a narrow and long steel plate produced by various steel rolling enterprises to meet the needs of industrialized production of various metal or mechanical products in different industrial sectors. At the end of the 20th century, the world's steel rolling technology developed rapidly, and steel rolling production has made great progress in automation, high precision and continuity. Strip steel is supplied in coils, with the advantages of high dimensional accuracy, good surface quality, easy processing and material saving. It is widely used in the production of welded steel pipes, as blanks for cold-bent steel, and in the manufacture of bicycle frames, wheel rims, clamps, washers, springs, saw blades and blades, soles of labor protection shoes and steel toe caps.
[0003] However, most of the current strip steel is produced through the hot rolling process. Hot-rolled steel plates are easy to process and have good ductility, but their hardness and strength are low, and their surface quality is poor. Surface oxidation, rust, pitting, etc. will occur. Moreover, hot-rolled steel plates are generally medium and thick plates, which cannot meet customers' requirements for strip steel size accuracy, plate shape, surface quality and thinner thickness. Summary of the invention
[0004] The purpose of the present invention is to propose a 0.8mm thick strip steel and a production process thereof. The production process method is simple, and the prepared 0.8mm thick strip steel has good mechanical properties, high hardness, stability, oxidation resistance and good machinability, can make the product thickness tolerance fluctuation small, the plate shape straightness is good, the surface quality is stable, and the controllable batch preparation can obtain thinner 0.8mm thick strip steel, which has broad application prospects.
[0005] The technical solution of the present invention is achieved in this way:
[0006] The present invention provides a production process for 0.8 mm thick strip steel, comprising the following steps:
[0007] S1. Raw material processing: 50Mn hot-rolled steel strip is used as raw material, and the surface oxide scale is removed by pickling;
[0008] S2. Hot rolling: The strip treated in step S1 is hot rolled and dephosphorized with high-pressure water;
[0009] S3. Intermediate annealing: annealing treatment is performed in the range of 735-740°C;
[0010] S4 cold rolling: cold rolling the strip after annealing in step S3 to a thickness of 0.5-0.7 mm;
[0011] S5. Hot-dip galvanizing: After the surface of the steel strip obtained in step S4 is degreased, it is hot-dip galvanized in a molten zinc solution, removed, purged and cooled;
[0012] S6 finished product annealing: the product in step S5 is annealed in the range of 570-600 ℃;
[0013] S7. Plate shape correction: The product in step S6 is subjected to plate shape correction according to a straightening reduction of 0.1-0.2 mm and an elongation of 0.2-0.5% to obtain a 0.8 mm thick strip.
[0014] As a further improvement of the present invention, the acid in step S1 is 0.1-0.5 mol / L hydrochloric acid or sulfuric acid; the process parameters of the hot rolling in step S2 are: the heating section temperature is 1200-1250°C, the soaking section temperature is 1200-1250°C, the furnace temperature is 1215-1220°C, the heating time is 110-150min, the final rolling temperature is 800-820°C, the coiling temperature is 560-570°C, and after rolling, the front section laminar cooling mode is adopted, and U-type cooling is performed. The coiling temperature of the head and tail 40-50m is 25-30°C higher than that of the middle part, and the pressure of the high-pressure water dephosphorization is 10-15Mpa.
[0015] As a further improvement of the present invention, the annealing treatment in step S3 adopts vertical furnace continuous annealing, the tension in the furnace is within 10N, the furnace temperature is controlled to 735-740°C, and the burn-through time per millimeter is controlled to 20-40s; the cold rolling in step S4 adopts a reduction rate of 65-72% and a cold rolling temperature of 400-420°C.
[0016] As a further improvement of the present invention, in step S5, a surfactant solution is used to remove grease, the surfactant is selected from at least one of Tween-20, Tween-40, Tween-60, and Tween-80, the concentration of the surfactant solution is 1-2wt%, the temperature of the molten zinc solution is 460-470°C, and it contains 2-4wt% of a plating aid, and the plating aid is Fe@graphene@Zn nanosheets; the annealing treatment in step S6 adopts vertical furnace continuous annealing, the tension in the furnace is within 15N, the furnace temperature is controlled to be 570-600°C, and the burn-through time per millimeter is controlled to be 20-40s.
[0017] As a further improvement of the present invention, the preparation method of the Fe@graphene@Zn nanosheets is as follows:
[0018] T1. Preparation of hollow alumina nanospheres: dissolving aluminum isopropoxide in dichloromethane to obtain an oil phase; dissolving an emulsifier in water to obtain an aqueous phase; dropping the aqueous phase into the oil phase, emulsifying, stirring to react, centrifuging, washing, drying, and calcining to obtain hollow alumina nanospheres;
[0019] T2. Preparation of ZnO-coated alumina hollow nanospheres: The alumina hollow nanospheres prepared in step T1 were added to water, citric acid and zinc salt were added, the reaction was heated and stirred, centrifuged, washed, and calcined to obtain ZnO-coated alumina hollow nanospheres;
[0020] T3. Preparation of graphene oxide @ ZnO coated alumina hollow nanospheres: adding the ZnO coated alumina hollow nanospheres prepared in step T2 to the graphene oxide aqueous dispersion, freeze-dried, to obtain graphene oxide @ ZnO coated alumina hollow nanospheres;
[0021] T4. Preparation of Fe2O3@graphene oxide@ZnO coated alumina hollow nanospheres: Add the graphene oxide@ZnO coated alumina hollow nanospheres prepared in step T3 to water, add citric acid and iron salt, heat and stir to react, centrifuge, wash, and calcine to obtain Fe2O3@graphene oxide@ZnO coated alumina hollow nanospheres;
[0022] T5. Preparation of nanosheets: The Fe2O3@graphene oxide@ZnO coated alumina hollow nanospheres prepared in step T4 were ball-milled to obtain Fe2O3@graphene oxide@ZnO coated alumina nanosheets;
[0023] T6. Removal of aluminum oxide: The Fe2O3@graphene oxide@ZnO coated aluminum oxide nanosheets prepared in step T5 were added to an alkaline solution and stirred to react to obtain Fe2O3@graphene oxide@ZnO nanosheets;
[0024] T7. Reduction: The Fe2O3@graphene oxide@ZnO nanosheets prepared in step T6 are reduced by hydrazine hydrate vapor to obtain Fe@graphene@Zn nanosheets.
[0025] As a further improvement of the present invention, the mass ratio of aluminum isopropoxide, dichloromethane, emulsifier and water in step T1 is 12-15:100-120:2-4:50-70, the emulsifier is selected from at least one of Tween-20, Tween-40, Tween-60 and Tween-80, the calcination temperature is 500-600°C, and the time is 1-3h; the mass ratio of alumina hollow nanospheres, citric acid and zinc salt in step T2 is 15-20:7-10:6-9, the zinc salt is selected from at least one of zinc chloride, zinc sulfate and zinc nitrate, the heating and stirring reaction temperature is 40-50°C, the time is 20-30min, and the calcination temperature is 500-600°C, and the time is 1-3h.
[0026] As a further improvement of the present invention, the concentration of the graphene oxide aqueous dispersion in step T3 is 0.5-1 mg / mL, and the mass ratio of the ZnO-coated alumina hollow nanospheres to the graphene oxide aqueous dispersion is 10-15:50; the mass ratio of the graphene oxide@ZnO-coated alumina hollow nanospheres, citric acid and iron salt in step T4 is 14-17:8-10:6-9, and the iron salt is selected from at least one of ferric chloride, ferric nitrate and ferric sulfate. The temperature of the heating and stirring reaction is 40-50°C, the time is 20-30min, and the calcination temperature is 300-400°C, and the time is 1-3h.
[0027] As a further improvement of the present invention, the ball milling time in step T5 is 1-2 hours; the alkali solution in step T6 is 10-15wt% NaOH or KOH solution, the stirring reaction temperature is 35-45°C, and the time is 0.5-1h; the reduction time in step T7 is 10-12h.
[0028] As a further improvement of the present invention, the preparation method of the Fe@graphene@Zn nanosheets is as follows:
[0029] T1. Preparation of hollow alumina nanospheres: dissolving 12-15 parts by weight of aluminum isopropoxide in 100-120 parts by weight of dichloromethane to obtain an oil phase; dissolving 2-4 parts by weight of an emulsifier in 50-70 parts by weight of water to obtain an aqueous phase; adding the aqueous phase dropwise to the oil phase, emulsifying, stirring the reaction, centrifuging, washing, drying, and calcining at 500-600°C for 1-3h to obtain hollow alumina nanospheres;
[0030] T2. Preparation of ZnO-coated alumina hollow nanospheres: 15-20 parts by weight of the alumina hollow nanospheres prepared in step T1 were added to 100 parts by weight of water, 7-10 parts by weight of citric acid and 6-9 parts by weight of zinc salt were added, heated to 40-50 ° C, stirred for 20-30 min, centrifuged, washed, calcined at 500-600 ° C for 1-3 h to obtain ZnO-coated alumina hollow nanospheres;
[0031] T3. Preparation of graphene oxide @ ZnO coated alumina hollow nanospheres: 10-15 parts by weight of the ZnO coated alumina hollow nanospheres prepared in step T2 were added to 50 parts by weight of 0.5-1 mg / mL of an aqueous dispersion of graphene oxide, and freeze-dried to obtain graphene oxide @ ZnO coated alumina hollow nanospheres;
[0032] T4. Preparation of Fe2O3@graphene oxide@ZnO coated alumina hollow nanospheres: 14-17 parts by weight of the graphene oxide@ZnO coated alumina hollow nanospheres prepared in step T3 were added to 100 parts by weight of water, 8-10 parts by weight of citric acid and 6-9 parts by weight of iron salt were added, heated to 40-50°C, stirred for 20-30min, centrifuged, washed, and calcined at 300-400°C for 1-3h to obtain Fe2O3@graphene oxide@ZnO coated alumina hollow nanospheres;
[0033] T5. Preparation of nanosheets: The Fe2O3@graphene oxide@ZnO coated alumina hollow nanospheres prepared in step T4 were ball-milled for 1-2h to obtain Fe2O3@graphene oxide@ZnO coated alumina nanosheets;
[0034] T6. Removal of aluminum oxide: The Fe2O3@graphene oxide@ZnO coated aluminum oxide nanosheets prepared in step T5 were added to a 10-15wt% NaOH or KOH solution, stirred at 35-45°C for 0.5-1h to obtain Fe2O3@graphene oxide@ZnO nanosheets;
[0035] T7. Reduction: The Fe2O3@graphene oxide@ZnO nanosheets prepared in step T6 are reduced with hydrazine hydrate vapor for 10-12 hours to obtain Fe@graphene@Zn nanosheets.
[0036] The present invention further protects a 0.8 mm thick strip steel produced by the above production process.
[0037] The present invention has the following beneficial effects:
[0038] The invention prepares a Fe@graphene@Zn nanosheet. Firstly, hollow aluminum oxide nanospheres are prepared by an emulsion method and a sol-gel method. A zinc oxide layer, a graphene oxide layer and an iron oxide layer are sequentially deposited on the surface of the hollow aluminum oxide nanospheres. After ball milling, Fe2O3@graphene oxide@ZnO coated aluminum oxide nanosheets are obtained. After aluminum oxide is reacted with an alkali to dissolve and remove, Fe2O3@graphene oxide@ZnO nanosheets are obtained. After hydrazine hydrate reduction, Fe@graphene@Zn nanosheets are obtained. Fe@graphene@Zn nanosheets are plating aids and are added to molten zinc liquid. When the zinc liquid is plated on the surface of the steel strip, Fe@graphene@Zn nanosheets are present at the two-phase interface of iron and zinc, and one side of Fe is in contact with the steel strip, and one side of Zn is in contact with the zinc liquid, which helps the mutual penetration of the same metals. After rolling, the thickness of the interface layer is reduced, and the bonding strength of the galvanized layer is improved, so that the stability, mechanical properties, flatness, oxidation resistance of the produced strip steel are better, and the surface roughness is smaller.
[0039] The continuous annealing process has a great influence on the mechanical properties of the product, eliminates the work hardening after cold rolling deformation, improves plasticity, and achieves different degrees of fine grain strengthening, solid solution strengthening, precipitation strengthening, phase transformation strengthening and dislocation strengthening. The comprehensive influence makes the finished product after deformation obtain the required organization and performance, eliminates yield flat strength, improves the surface quality of the galvanized layer of the strip steel, and ensures the surface roughness requirements, which is beneficial to the user's processing and forming. The present invention adopts the combination of intermediate annealing + finished product annealing process, so that the mechanical properties of the obtained strip steel material are enhanced, the elongation at break and the tensile strength are improved, and the yield strength is improved.
[0040] Hot rolling heats the steel billet to the temperature range of the austenite single phase region, giving it a high temperature and sufficient time to homogenize the structure and dissolve carbides. By reasonably controlling the heating temperature of hot rolling, the coarsening of austenite grains is avoided, which affects the structure and properties of the strip after hot rolling.
[0041] The hot-rolled product is cold-rolled to the target thickness, so that the grains of the strip are broken, which is beneficial to improve the cold rolling deformation energy storage and increase the recrystallization driving force during the hot-dip galvanizing process annealing.
[0042] The production process method of the 0.8 mm thick strip steel of the present invention is simple, and the prepared 0.8 mm thick strip steel has good mechanical properties, high hardness, stability, good oxidation resistance and machinability, can reduce the fluctuation of product thickness tolerance, has good plate shape straightness, and has stable surface quality, and can controllably prepare thinner 0.8 mm thick strip steel in batches, which has broad application prospects. DETAILED DESCRIPTION
[0043] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0044] The 50Mn hot-rolled steel strip was purchased from Shandong Liugang Metal Technology Co., Ltd. It is a high-quality carbon structural steel, a medium-carbon manganese-containing steel. The chemical composition complies with the provisions of GB / T699-2015 "High-quality Carbon Structural Steel", and the mechanical properties comply with the national standard GB / T8749-2021 "High-quality Carbon Structural Steel Hot-rolled Steel Strip".
[0045] Graphene oxide is commercially available or prepared by the following method:
[0046] Step 1: Weigh 10 g of natural graphite powder, 4 g of potassium persulfate, and 10 g of phosphorus pentoxide, add them into a three-necked flask containing 25 mL of sulfuric acid (analytical grade), react in a constant temperature water bath at 60 ° C for 3 h, then move into a constant temperature water bath at 25 ° C for 5 h, filter, wash with deionized water to neutrality, and dry in air to obtain pre-oxidized graphite;
[0047] Step 2: Weigh 1g of pre-oxidized graphite, add 25mL of sulfuric acid while stirring, put it in an ice water bath, and after the pre-oxidized graphite is completely dissolved, add 3g of potassium permanganate, react for 2h, then move to a constant temperature water bath at 35°C to react for 40min, add deionized water, continue to react at 35°C for 1h, and finally add 30% H2O2 until no gas is generated and the solution turns bright yellow. Centrifuge and filter while hot, and wash with a large amount of 5% hydrochloric acid and deionized water until neutral. After the final precipitate is ultrasonically shaken for 1h, pour it into a culture dish and dry it at 90°C for 24h to obtain graphene oxide.
[0048] Preparation Example 1 Preparation of Fe@graphene@Zn nanosheets
[0049] The specific method is as follows:
[0050] T1. Preparation of hollow alumina nanospheres: 12 parts by weight of aluminum isopropoxide were dissolved in 100 parts by weight of dichloromethane to obtain an oil phase; 2 parts by weight of Tween-40 were dissolved in 50 parts by weight of water to obtain an aqueous phase; the aqueous phase was added dropwise to the oil phase, emulsified at 7000 r / min for 15 min, stirred for reaction for 20 min, centrifuged, washed, dried, and calcined at 500° C. for 1 h to obtain hollow alumina nanospheres;
[0051] T2. Preparation of ZnO-coated alumina hollow nanospheres: 15 parts by weight of the alumina hollow nanospheres prepared in step T1 were added to 100 parts by weight of water, 7 parts by weight of citric acid and 6 parts by weight of zinc chloride were added, heated to 40 ° C, stirred for 20 min, centrifuged, washed, and calcined at 500 ° C for 1 h to obtain ZnO-coated alumina hollow nanospheres;
[0052] T3. Preparation of graphene oxide @ ZnO coated alumina hollow nanospheres: 10 parts by weight of ZnO coated alumina hollow nanospheres prepared in step T2 were added to 50 parts by weight of 0.5 mg / mL graphene oxide aqueous dispersion, freeze-dried to obtain graphene oxide @ ZnO coated alumina hollow nanospheres;
[0053] T4. Preparation of Fe2O3@graphene oxide@ZnO coated alumina hollow nanospheres: 14 parts by weight of the graphene oxide@ZnO coated alumina hollow nanospheres prepared in step T3 were added to 100 parts by weight of water, 8 parts by weight of citric acid and 6 parts by weight of ferric chloride were added, heated to 40°C, stirred for 20 minutes, centrifuged, washed, and calcined at 300°C for 1 hour to obtain Fe2O3@graphene oxide@ZnO coated alumina hollow nanospheres;
[0054] T5. Preparation of nanosheets: The Fe2O3@graphene oxide@ZnO coated alumina hollow nanospheres prepared in step T4 were ball-milled for 1 h to obtain Fe2O3@graphene oxide@ZnO coated alumina nanosheets;
[0055] T6. Removal of aluminum oxide: The Fe2O3@graphene oxide@ZnO coated aluminum oxide nanosheets prepared in step T5 were added to a 10 wt% NaOH solution and stirred at 35°C for 0.5 h to obtain Fe2O3@graphene oxide@ZnO nanosheets;
[0056] T7. Reduction: The Fe2O3@graphene oxide@ZnO nanosheets prepared in step T6 are reduced with hydrazine hydrate vapor for 10 h to obtain Fe@graphene@Zn nanosheets.
[0057] Preparation Example 2 Preparation of Fe@graphene@Zn nanosheets
[0058] The specific method is as follows:
[0059] T1. Preparation of hollow alumina nanospheres: 15 parts by weight of aluminum isopropoxide was dissolved in 120 parts by weight of dichloromethane to obtain an oil phase; 4 parts by weight of Tween-60 was dissolved in 70 parts by weight of water to obtain an aqueous phase; the aqueous phase was added dropwise to the oil phase, emulsified at 7000 r / min for 15 min, stirred for 40 min, centrifuged, washed, dried, and calcined at 600°C for 3 h to obtain hollow alumina nanospheres;
[0060] T2. Preparation of ZnO-coated alumina hollow nanospheres: 20 parts by weight of the alumina hollow nanospheres prepared in step T1 were added to 100 parts by weight of water, 10 parts by weight of citric acid and 9 parts by weight of zinc nitrate were added, heated to 50 ° C, stirred for 30 min, centrifuged, washed, and calcined at 600 ° C for 3 h to obtain ZnO-coated alumina hollow nanospheres;
[0061] T3. Preparation of graphene oxide @ ZnO coated alumina hollow nanospheres: 15 parts by weight of ZnO coated alumina hollow nanospheres prepared in step T2 were added to 50 parts by weight of 1 mg / mL graphene oxide aqueous dispersion, freeze-dried to obtain graphene oxide @ ZnO coated alumina hollow nanospheres;
[0062] T4. Preparation of Fe2O3@graphene oxide@ZnO coated alumina hollow nanospheres: 17 parts by weight of the graphene oxide@ZnO coated alumina hollow nanospheres prepared in step T3 were added to 100 parts by weight of water, 10 parts by weight of citric acid and 9 parts by weight of ferric nitrate were added, heated to 50°C, stirred for 30 minutes, centrifuged, washed, and calcined at 400°C for 3 hours to obtain Fe2O3@graphene oxide@ZnO coated alumina hollow nanospheres;
[0063] T5. Preparation of nanosheets: The Fe2O3@graphene oxide@ZnO coated alumina hollow nanospheres prepared in step T4 were ball-milled for 2 h to obtain Fe2O3@graphene oxide@ZnO coated alumina nanosheets;
[0064] T6. Removal of aluminum oxide: The Fe2O3@graphene oxide@ZnO coated aluminum oxide nanosheets prepared in step T5 were added to a 15 wt% KOH solution and stirred at 45°C for 1 h to obtain Fe2O3@graphene oxide@ZnO nanosheets;
[0065] T7. Reduction: The Fe2O3@graphene oxide@ZnO nanosheets prepared in step T6 are reduced with hydrazine hydrate vapor for 12 h to obtain Fe@graphene@Zn nanosheets.
[0066] Preparation Example 3 Preparation of Fe@graphene@Zn nanosheets
[0067] The specific method is as follows:
[0068] T1. Preparation of hollow alumina nanospheres: 13 parts by weight of aluminum isopropoxide was dissolved in 110 parts by weight of dichloromethane to obtain an oil phase; 3 parts by weight of Tween-80 was dissolved in 60 parts by weight of water to obtain an aqueous phase; the aqueous phase was added dropwise to the oil phase, emulsified at 7000 r / min for 15 min, stirred for reaction for 30 min, centrifuged, washed, dried, and calcined at 550° C. for 2 h to obtain hollow alumina nanospheres;
[0069] T2. Preparation of ZnO-coated alumina hollow nanospheres: 17 parts by weight of the alumina hollow nanospheres prepared in step T1 were added to 100 parts by weight of water, 9 parts by weight of citric acid and 7 parts by weight of zinc sulfate were added, heated to 45 ° C, stirred for 25 min, centrifuged, washed, calcined at 550 ° C for 2 h to obtain ZnO-coated alumina hollow nanospheres;
[0070] T3. Preparation of graphene oxide @ ZnO coated alumina hollow nanospheres: 12 parts by weight of ZnO coated alumina hollow nanospheres prepared in step T2 were added to 50 parts by weight of 0.5 mg / mL graphene oxide aqueous dispersion, freeze-dried to obtain graphene oxide @ ZnO coated alumina hollow nanospheres;
[0071] T4. Preparation of Fe2O3@graphene oxide@ZnO coated alumina hollow nanospheres: 15 parts by weight of the graphene oxide@ZnO coated alumina hollow nanospheres prepared in step T3 were added to 100 parts by weight of water, 9 parts by weight of citric acid and 7 parts by weight of ferric sulfate were added, heated to 45°C, stirred for 25 minutes, centrifuged, washed, and calcined at 350°C for 2 hours to obtain Fe2O3@graphene oxide@ZnO coated alumina hollow nanospheres;
[0072] T5. Preparation of nanosheets: The Fe2O3@graphene oxide@ZnO coated alumina hollow nanospheres prepared in step T4 were ball-milled for 1.5 h to obtain Fe2O3@graphene oxide@ZnO coated alumina nanosheets;
[0073] T6. Removal of aluminum oxide: The Fe2O3@graphene oxide@ZnO coated aluminum oxide nanosheets prepared in step T5 were added to a 12 wt% NaOH solution and stirred at 40°C for 1 h to obtain Fe2O3@graphene oxide@ZnO nanosheets;
[0074] T7. Reduction: The Fe2O3@graphene oxide@ZnO nanosheets prepared in step T6 are reduced with hydrazine hydrate vapor for 11 h to obtain Fe@graphene@Zn nanosheets.
[0075] Comparative Preparation Example 1
[0076] Compared with Preparation Example 3, the difference is that step T7 is not performed.
[0077] Comparative Preparation Example 2
[0078] Compared with Preparation Example 3, the difference is that step T6 is not performed.
[0079] Example 1
[0080] This embodiment provides a production process for 0.8 mm thick strip steel, comprising the following steps:
[0081] S1. Raw material processing: 50Mn hot-rolled steel strip is used as raw material, and the surface oxide scale is removed by washing with 0.1mol / L hydrochloric acid;
[0082] S2. Hot rolling: The strip treated in step S1 is hot rolled and dephosphorized with 10Mpa high pressure water;
[0083] The process parameters of the hot rolling are as follows: the temperature of the heating section is 1200°C, the temperature of the soaking section is 1200°C, the furnace temperature is 1215°C, the heating time is 110min, the final rolling temperature is 800°C, the coiling temperature is 560°C, the front section laminar cooling mode is adopted after rolling, and U-shaped cooling is performed, and the coiling temperature of the head and tail 40m is 25°C higher than that of the middle part;
[0084] S3. Intermediate annealing: Continuous annealing in a vertical furnace, with the tension in the furnace within 10N, the furnace temperature controlled at 735℃, and the burn-through time per millimeter controlled at 20s;
[0085] S4 cold rolling: the strip after annealing in step S3 is subjected to a reduction ratio of 65% and a cold rolling temperature of 400°C to a thickness of 0.7 mm;
[0086] S5. Hot-dip galvanizing: The steel strip obtained in step S4 is subjected to a 1 wt % Tween-60 solution to remove grease from the surface, and then placed in a 460° C. molten zinc solution (containing 2 wt % of the Fe@graphene@Zn nanosheet plating aid obtained in Preparation Example 1) for hot-dip galvanizing, and then taken out, purged and cooled;
[0087] S6 finished product annealing: The product in step S5 is annealed in a vertical furnace, the furnace tension is within 15N, the furnace temperature is controlled at 570°C, and the burn-through time per millimeter is controlled at 20s;
[0088] S7. Plate shape correction: The product in step S6 is subjected to plate shape correction according to a tensile correction reduction of 0.1 mm and an elongation of 0.2% to obtain a 0.8 mm thick strip steel.
[0089] Example 2
[0090] This embodiment provides a production process for 0.8 mm thick strip steel, comprising the following steps:
[0091] S1. Raw material processing: 50Mn hot-rolled steel strip is used as raw material, and the surface oxide scale is removed by washing with 0.5mol / L sulfuric acid;
[0092] S2. Hot rolling: The strip treated in step S1 is hot rolled and dephosphorized with 15Mpa high pressure water;
[0093] The process parameters of the hot rolling are as follows: the temperature of the heating section is 1250°C, the temperature of the soaking section is 1250°C, the furnace temperature is 1220°C, the heating time is 150min, the final rolling temperature is 820°C, the coiling temperature is 570°C, the front section laminar cooling mode is adopted after rolling, and U-shaped cooling is performed, and the coiling temperature of the head and tail 50m is 30°C higher than that of the middle part;
[0094] S3. Intermediate annealing: Continuous annealing in a vertical furnace, with the tension in the furnace within 10N, the furnace temperature controlled at 740℃, and the burn-through time per millimeter controlled at 40s;
[0095] S4 cold rolling: the strip after annealing in step S3 is subjected to a reduction ratio of 72% and a cold rolling temperature of 420°C to a thickness of 0.7 mm;
[0096] S5. Hot-dip galvanizing: The strip steel obtained in step S4 is subjected to a 2 wt % Tween-20 solution to remove grease from the surface, and then placed in a 470° C. molten zinc solution (containing 4 wt % of the Fe@graphene@Zn nanosheet plating aid obtained in Preparation Example 2) for hot-dip galvanizing, and then taken out, purged and cooled;
[0097] S6 finished product annealing: The product in step S5 is annealed in a vertical furnace, the furnace tension is within 15N, the furnace temperature is controlled at 600°C, and the burn-through time per millimeter is controlled at 40s;
[0098] S7. Plate shape correction: The product in step S6 is subjected to plate shape correction according to a straightening reduction of 0.2 mm and an elongation of 0.5% to obtain a 0.8 mm thick strip.
[0099] Example 3
[0100] This embodiment provides a production process for 0.8 mm thick strip steel, comprising the following steps:
[0101] S1. Raw material processing: 50Mn hot-rolled steel strip is used as raw material, and the surface oxide scale is removed by washing with 0.3mol / L hydrochloric acid;
[0102] S2. Hot rolling: The strip treated in step S1 is hot rolled and dephosphorized with 12Mpa high pressure water;
[0103] The process parameters of the hot rolling are as follows: the temperature of the heating section is 1220°C, the temperature of the soaking section is 1220°C, the temperature of the furnace is 1218°C, the heating time is 130min, the final rolling temperature is 810°C, the coiling temperature is 565°C, the front section laminar cooling mode is adopted after rolling, and U-shaped cooling is performed, and the coiling temperature of the head and tail 45m is 27°C higher than that of the middle part;
[0104] S3. Intermediate annealing: Continuous annealing in a vertical furnace, with the tension in the furnace within 10N, the furnace temperature controlled at 738°C, and the burn-through time per millimeter controlled at 30s;
[0105] S4 cold rolling: the strip after annealing in step S3 is subjected to a reduction ratio of 69% and a cold rolling temperature of 410°C to a thickness of 0.7 mm;
[0106] S5. Hot-dip galvanizing: The strip steel obtained in step S4 is subjected to surface degreasing with 1.5 wt% Tween-80 solution, and then placed in a 465°C molten zinc solution (containing 3 wt% of the Fe@graphene@Zn nanosheet plating aid obtained in Preparation Example 3) for hot-dip galvanizing, and then taken out, purged and cooled;
[0107] S6 finished product annealing: The product in step S5 is annealed in a vertical furnace, the furnace tension is within 15N, the furnace temperature is controlled at 585°C, and the burn-through time per millimeter is controlled at 30s;
[0108] S7. Plate shape correction: The product in step S6 is subjected to plate shape correction according to a tensile correction reduction of 0.15 mm and an elongation of 0.35% to obtain a 0.8 mm thick strip steel.
[0109] Comparative Example 1
[0110] Compared with Example 3, the difference is that the Fe@graphene@Zn nanosheet plating assistant is prepared by Comparative Preparation Example 1.
[0111] Comparative Example 2
[0112] Compared with Example 3, the difference is that the Fe@graphene@Zn nanosheet plating assistant is prepared by Comparative Preparation Example 2.
[0113] Comparative Example 3
[0114] Compared with Example 3, the difference is that no Fe@graphene@Zn nanosheet plating aid is added.
[0115] The details are as follows:
[0116] S1. Raw material processing: 50Mn hot-rolled steel strip is used as raw material, and the surface oxide scale is removed by washing with 0.3mol / L hydrochloric acid;
[0117] S2. Hot rolling: The strip treated in step S1 is hot rolled and dephosphorized with 12Mpa high pressure water;
[0118] The process parameters of the hot rolling are as follows: the temperature of the heating section is 1220°C, the temperature of the soaking section is 1220°C, the temperature of the furnace is 1218°C, the heating time is 130min, the final rolling temperature is 810°C, the coiling temperature is 565°C, the front section laminar cooling mode is adopted after rolling, and U-shaped cooling is performed, and the coiling temperature of the head and tail 45m is 27°C higher than that of the middle part;
[0119] S3. Intermediate annealing: Continuous annealing in a vertical furnace, with the tension in the furnace within 10N, the furnace temperature controlled at 738°C, and the burn-through time per millimeter controlled at 30s;
[0120] S4 cold rolling: the strip after annealing in step S3 is subjected to a reduction ratio of 69% and a cold rolling temperature of 410°C to a thickness of 0.7 mm;
[0121] S5. Hot-dip galvanizing: The strip obtained in step S4 is subjected to surface grease removal by 1.5wt% Tween-80 solution, and then hot-dip galvanizing is performed in a molten zinc solution at 465°C, and then removed, purged and cooled;
[0122] S6 finished product annealing: The product in step S5 is annealed in a vertical furnace, the furnace tension is within 15N, the furnace temperature is controlled at 585°C, and the burn-through time per millimeter is controlled at 30s;
[0123] S7. Plate shape correction: The product in step S6 is subjected to plate shape correction according to a tensile correction reduction of 0.15 mm and an elongation of 0.35% to obtain a 0.8 mm thick strip steel.
[0124] Comparative Example 4
[0125] Compared with Example 3, the difference is that step S2 is not performed.
[0126] The details are as follows:
[0127] S1. Raw material processing: 50Mn hot-rolled steel strip is used as raw material, and the surface oxide scale is removed by washing with 0.3mol / L hydrochloric acid;
[0128] S2. Intermediate annealing: Continuous annealing in a vertical furnace, with the tension in the furnace within 10N, the furnace temperature controlled at 738℃, and the burn-through time per millimeter controlled at 30s;
[0129] S3 cold rolling: the strip after annealing in step S2 is subjected to a reduction ratio of 69% and a cold rolling temperature of 410°C to a thickness of 0.7 mm;
[0130] S4. Hot-dip galvanizing: The strip steel obtained in step S3 is subjected to surface degrease by using 1.5 wt% Tween-80 solution, and then placed in a 465°C molten zinc solution (containing 3 wt% of the Fe@graphene@Zn nanosheet plating aid obtained in Preparation Example 3) for hot-dip galvanizing, and then taken out, purged and cooled;
[0131] S5 finished product annealing: The product in step S4 is annealed in a vertical furnace, the furnace tension is within 15N, the furnace temperature is controlled at 585°C, and the burn-through time per millimeter is controlled at 30s;
[0132] S6. Plate shape correction: The product in step S5 is subjected to plate shape correction according to a tensile correction reduction of 0.15 mm and an elongation of 0.35% to obtain a 0.8 mm thick strip steel.
[0133] Comparative Example 5
[0134] Compared with Example 3, the difference is that step S4 is not performed.
[0135] The details are as follows:
[0136] S1. Raw material processing: 50Mn hot-rolled steel strip is used as raw material, and the surface oxide scale is removed by washing with 0.3mol / L hydrochloric acid;
[0137] S2. Hot rolling: The strip treated in step S1 is hot rolled and dephosphorized with 12Mpa high pressure water;
[0138] The process parameters of the hot rolling are as follows: the temperature of the heating section is 1220°C, the temperature of the soaking section is 1220°C, the temperature of the furnace is 1218°C, the heating time is 130min, the final rolling temperature is 810°C, the coiling temperature is 565°C, the front section laminar cooling mode is adopted after rolling, and U-shaped cooling is performed, and the coiling temperature of the head and tail 45m is 27°C higher than that of the middle part;
[0139] S3. Intermediate annealing: Continuous annealing in a vertical furnace, with the tension in the furnace within 10N, the furnace temperature controlled at 738°C, and the burn-through time per millimeter controlled at 30s;
[0140] S4. Hot-dip galvanizing: The strip steel obtained in step S3 is subjected to surface degrease by using 1.5 wt% Tween-80 solution, and then placed in a 465°C molten zinc solution (containing 3 wt% of the Fe@graphene@Zn nanosheet plating aid obtained in Preparation Example 3) for hot-dip galvanizing, and then taken out, purged and cooled;
[0141] S5 finished product annealing: The product in step S4 is annealed in a vertical furnace, the furnace tension is within 15N, the furnace temperature is controlled at 585°C, and the burn-through time per millimeter is controlled at 30s;
[0142] S6. Plate shape correction: The product in step S5 is subjected to plate shape correction according to a tensile correction reduction of 0.15 mm and an elongation of 0.35% to obtain a 0.8 mm thick strip steel.
[0143] Comparative Example 6
[0144] Compared with Example 3, the difference is that step S3 is not performed.
[0145] The details are as follows:
[0146] S1. Raw material processing: 50Mn hot-rolled steel strip is used as raw material, and the surface oxide scale is removed by washing with 0.3mol / L hydrochloric acid;
[0147] S2. Hot rolling: The strip treated in step S1 is hot rolled and dephosphorized with 12Mpa high pressure water;
[0148] The process parameters of the hot rolling are as follows: the temperature of the heating section is 1220°C, the temperature of the soaking section is 1220°C, the temperature of the furnace is 1218°C, the heating time is 130min, the final rolling temperature is 810°C, the coiling temperature is 565°C, the front section laminar cooling mode is adopted after rolling, and U-shaped cooling is performed, and the coiling temperature of the head and tail 45m is 27°C higher than that of the middle part;
[0149] S3 cold rolling: the strip in step S2 is rolled at a reduction rate of 69% and a cold rolling temperature of 410°C to a thickness of 0.7 mm;
[0150] S4. Hot-dip galvanizing: The strip steel obtained in step S3 is subjected to surface degrease by using 1.5 wt% Tween-80 solution, and then placed in a 465°C molten zinc solution (containing 3 wt% of the Fe@graphene@Zn nanosheet plating aid obtained in Preparation Example 3) for hot-dip galvanizing, and then taken out, purged and cooled;
[0151] S5 finished product annealing: The product in step S4 is annealed in a vertical furnace, the furnace tension is within 15N, the furnace temperature is controlled at 585°C, and the burn-through time per millimeter is controlled at 30s;
[0152] S6. Plate shape correction: The product in step S5 is subjected to plate shape correction according to a tensile correction reduction of 0.15 mm and an elongation of 0.35% to obtain a 0.8 mm thick strip steel.
[0153] Comparative Example 7
[0154] Compared with the embodiment 3, the difference is that step S6 is not performed.
[0155] The details are as follows:
[0156] S1. Raw material processing: 50Mn hot-rolled steel strip is used as raw material, and the surface oxide scale is removed by washing with 0.3mol / L hydrochloric acid;
[0157] S2. Hot rolling: The strip treated in step S1 is hot rolled and dephosphorized with 12Mpa high pressure water;
[0158] The process parameters of the hot rolling are as follows: the temperature of the heating section is 1220°C, the temperature of the soaking section is 1220°C, the temperature of the furnace is 1218°C, the heating time is 130min, the final rolling temperature is 810°C, the coiling temperature is 565°C, the front section laminar cooling mode is adopted after rolling, and U-shaped cooling is performed, and the coiling temperature of the head and tail 45m is 27°C higher than that of the middle part;
[0159] S3. Intermediate annealing: Continuous annealing in a vertical furnace, with the tension in the furnace within 10N, the furnace temperature controlled at 738°C, and the burn-through time per millimeter controlled at 30s;
[0160] S4 cold rolling: the strip after annealing in step S3 is subjected to a reduction ratio of 69% and a cold rolling temperature of 410°C to a thickness of 0.7 mm;
[0161] S5. Hot-dip galvanizing: The strip steel obtained in step S4 is subjected to surface degreasing with 1.5 wt% Tween-80 solution, and then placed in a 465°C molten zinc solution (containing 3 wt% of the Fe@graphene@Zn nanosheet plating aid obtained in Preparation Example 3) for hot-dip galvanizing, and then taken out, purged and cooled;
[0162] S6. Plate shape correction: The product in step S5 is subjected to plate shape correction according to a tensile correction reduction of 0.15 mm and an elongation of 0.35% to obtain a 0.8 mm thick strip steel.
[0163] Test Example 1
[0164] The 0.8 mm thick strip steels prepared in Examples 1-3 and Comparative Examples 1-7 of the present invention were subjected to mechanical property tests. The strip steels were sampled according to GB / T 2975-1998 "Sampling location and sample preparation for mechanical property tests of steel and steel products", and the sampling location was 1 / 4 of the width of the middle part of the strip steel; the tensile test was carried out on a Zwick tensile testing machine according to GB / T 228.1-2010 "Metallic material tensile test Part 1: Room temperature test method" to detect its mechanical properties, and the tensile sample direction was longitudinal. The results are shown in Table 1.
[0165] Table 1
[0166] Group Yield strength(MPa) Tensile strength(MPa) Elongation at break (%) Example 1 682 704 32 Example 2 689 710 33 Example 3 694 715 35 Comparative Example 1 667 687 29 Comparative Example 2 652 664 27 Comparative Example 3 621 635 22 Comparative Example 4 670 682 25 Comparative Example 5 645 658 21 Comparative Example 6 639 654 23 Comparative Example 7 630 647 19
[0167] It can be seen from the above table that the 0.8 mm thick strip steels prepared in Examples 1-3 of the present invention have good mechanical properties.
[0168] Test Example 2
[0169] The 0.8 mm thick strip steels prepared in Examples 1-3 of the present invention and Comparative Examples 1-7 were subjected to performance tests. The results are shown in Table 2.
[0170] Table 2
[0171]
[0172]
[0173] It can be seen from the above table that the 0.8 mm thick strip steels prepared in Examples 1-3 of the present invention have better comprehensive properties.
[0174] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A production process for 0.8 mm thick strip steel, characterized in that: The following steps are involved: S1. Raw material processing: 50Mn hot-rolled steel strip is used as raw material, and the surface oxide scale is removed by pickling; S2. Hot rolling: The strip treated in step S1 is hot rolled and dephosphorized with high-pressure water; S3. Intermediate annealing: annealing treatment is performed in the range of 735-740°C; S4 cold rolling: cold rolling the strip after annealing in step S3 to a thickness of 0.5-0.7 mm; S5. Hot-dip galvanizing: After the surface of the steel strip obtained in step S4 is degreased, it is hot-dip galvanized in a molten zinc solution, removed, purged and cooled; A surfactant solution is used to remove grease, wherein the surfactant is selected from at least one of Tween-20, Tween-40, Tween-60, and Tween-80, the concentration of the surfactant solution is 1-2wt%, the temperature of the molten zinc solution is 460-470° C., and the molten zinc solution contains 2-4wt% of a plating aid, wherein the plating aid is Fe@graphene@Zn nanosheets; S6 finished product annealing: the product in step S5 is annealed in the range of 570-600 ℃; the annealing treatment is carried out in a vertical furnace for continuous annealing, the furnace tension is within 15N, the furnace temperature is controlled at 570-600 ℃, and the burn-through time per millimeter is controlled at 20-40s; S7. Plate shape correction: The product in step S6 is corrected according to the tension correction reduction of 0.1-0.2mm and the elongation of 0.2-0.5% to obtain a 0.8mm thick strip; The preparation method of the Fe@graphene@Zn nanosheets is as follows: T1. Preparation of hollow alumina nanospheres: dissolving aluminum isopropoxide in dichloromethane to obtain an oil phase; dissolving an emulsifier in water to obtain an aqueous phase; dropping the aqueous phase into the oil phase, emulsifying, stirring to react, centrifuging, washing, drying, and calcining to obtain hollow alumina nanospheres; T2. Preparation of ZnO-coated alumina hollow nanospheres: The alumina hollow nanospheres prepared in step T1 were added to water, citric acid and zinc salt were added, the reaction was heated and stirred, centrifuged, washed, and calcined to obtain ZnO-coated alumina hollow nanospheres; T3. Preparation of graphene oxide @ ZnO coated alumina hollow nanospheres: adding the ZnO coated alumina hollow nanospheres prepared in step T2 to the graphene oxide aqueous dispersion, freeze-dried, to obtain graphene oxide @ ZnO coated alumina hollow nanospheres; T4. Preparation of Fe2O3@graphene oxide@ZnO coated alumina hollow nanospheres: Add the graphene oxide@ZnO coated alumina hollow nanospheres prepared in step T3 to water, add citric acid and iron salt, heat and stir to react, centrifuge, wash, and calcine to obtain Fe2O3@graphene oxide@ZnO coated alumina hollow nanospheres; T5. Preparation of nanosheets: The Fe2O3@graphene oxide@ZnO coated alumina hollow nanospheres prepared in step T4 were ball-milled to obtain Fe2O3@graphene oxide@ZnO coated alumina nanosheets; T6. Removal of aluminum oxide: The Fe2O3@graphene oxide@ZnO coated aluminum oxide nanosheets prepared in step T5 were added to an alkaline solution and stirred to react to obtain Fe2O3@graphene oxide@ZnO nanosheets; T7. Reduction: The Fe2O3@graphene oxide@ZnO nanosheets prepared in step T6 are reduced by hydrazine hydrate vapor to obtain Fe@graphene@Zn nanosheets.
2. The production process according to claim 1, characterized in that: The acid in step S1 is 0.1-0.5 mol / L hydrochloric acid or sulfuric acid; the process parameters of the hot rolling in step S2 are: the temperature of the heating section is 1200-1250°C, the temperature of the soaking section is 1200-1250°C, the furnace temperature is 1215-1220°C, the heating time is 110-150min, the final rolling temperature is 800-820°C, the coiling temperature is 560-570°C, the front section laminar cooling mode is adopted after rolling, and U-type cooling is performed, the coiling temperature of the head and tail 40-50m is 25-30°C higher than that of the middle part, and the pressure of the high-pressure water dephosphorization is 10-15MPa.
3. The production process according to claim 1, characterized in that: The annealing treatment in step S3 adopts vertical furnace continuous annealing, the tension in the furnace is within 10N, the furnace temperature is controlled at 735-740℃, and the burn-through time per millimeter is controlled at 20-40s; the cold rolling in step S4 adopts a reduction rate of 65-72% and a cold rolling temperature of 400-420℃.
4. The production process according to claim 1, characterized in that: The mass ratio of aluminum isopropoxide, dichloromethane, emulsifier and water in step T1 is 12-15:100-120:2-4:50-70, the emulsifier is selected from at least one of Tween-20, Tween-40, Tween-60 and Tween-80, the calcination temperature is 500-600°C, and the time is 1-3h; the mass ratio of alumina hollow nanospheres, citric acid and zinc salt in step T2 is 15-20:7-10:6-9, the zinc salt is selected from at least one of zinc chloride, zinc sulfate and zinc nitrate, the heating and stirring reaction temperature is 40-50°C, the time is 20-30min, and the calcination temperature is 500-600°C, and the time is 1-3h.
5. The production process according to claim 1, characterized in that: The concentration of the graphene oxide aqueous dispersion in step T3 is 0.5-1 mg / mL, and the mass ratio of the ZnO-coated alumina hollow nanospheres to the graphene oxide aqueous dispersion is 10-15:50; the mass ratio of the graphene oxide@ZnO-coated alumina hollow nanospheres, citric acid and iron salt in step T4 is 14-17:8-10:6-9, and the iron salt is selected from at least one of ferric chloride, ferric nitrate and ferric sulfate. The temperature of the heating and stirring reaction is 40-50°C, the time is 20-30min, and the calcination temperature is 300-400°C, and the time is 1-3h.
6. The production process according to claim 1, characterized in that: The ball milling time in step T5 is 1-2 hours; the alkali solution in step T6 is 10-15wt% NaOH or KOH solution, the stirring reaction temperature is 35-45°C, and the time is 0.5-1h; the reduction time in step T7 is 10-12h.
7. The production process according to claim 1, characterized in that: The preparation method of the Fe@graphene@Zn nanosheets is as follows: T1. Preparation of hollow alumina nanospheres: dissolving 12-15 parts by weight of aluminum isopropoxide in 100-120 parts by weight of dichloromethane to obtain an oil phase; dissolving 2-4 parts by weight of an emulsifier in 50-70 parts by weight of water to obtain an aqueous phase; adding the aqueous phase dropwise to the oil phase, emulsifying, stirring the reaction, centrifuging, washing, drying, and calcining at 500-600°C for 1-3h to obtain hollow alumina nanospheres; T2. Preparation of ZnO-coated alumina hollow nanospheres: 15-20 parts by weight of the alumina hollow nanospheres prepared in step T1 were added to 100 parts by weight of water, 7-10 parts by weight of citric acid and 6-9 parts by weight of zinc salt were added, heated to 40-50 ° C, stirred for 20-30 min, centrifuged, washed, calcined at 500-600 ° C for 1-3 h to obtain ZnO-coated alumina hollow nanospheres; T3. Preparation of graphene oxide @ ZnO coated alumina hollow nanospheres: 10-15 parts by weight of the ZnO coated alumina hollow nanospheres prepared in step T2 were added to 50 parts by weight of 0.5-1 mg / mL of an aqueous dispersion of graphene oxide, and freeze-dried to obtain graphene oxide @ ZnO coated alumina hollow nanospheres; T4. Preparation of Fe2O3@graphene oxide@ZnO coated alumina hollow nanospheres: 14-17 parts by weight of the graphene oxide@ZnO coated alumina hollow nanospheres prepared in step T3 were added to 100 parts by weight of water, 8-10 parts by weight of citric acid and 6-9 parts by weight of iron salt were added, heated to 40-50°C, stirred for 20-30min, centrifuged, washed, and calcined at 300-400°C for 1-3h to obtain Fe2O3@graphene oxide@ZnO coated alumina hollow nanospheres; T5. Preparation of nanosheets: The Fe2O3@graphene oxide@ZnO coated alumina hollow nanospheres prepared in step T4 were ball-milled for 1-2h to obtain Fe2O3@graphene oxide@ZnO coated alumina nanosheets; T6. Removal of aluminum oxide: The Fe2O3@graphene oxide@ZnO coated aluminum oxide nanosheets prepared in step T5 were added to a 10-15wt% NaOH or KOH solution, stirred at 35-45°C for 0.5-1h to obtain Fe2O3@graphene oxide@ZnO nanosheets; T7. Reduction: The Fe2O3@graphene oxide@ZnO nanosheets prepared in step T6 are reduced with hydrazine hydrate vapor for 10-12 hours to obtain Fe@graphene@Zn nanosheets.
8. A 0.8 mm thick strip steel produced by the production process according to any one of claims 1 to 7.
Citation Information
Patent Citations
Synthesis method for aluminium oxide nano hollow ball-in-ball
CN103771470A
Steel strip, sheet or blank having improved formability and method to produce such strip
CN112166203A